Supply Chain Control: a Theory of Vertical Integration - Giovanni Ursino (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2015)
Improving a company's bargaining position is often cited as a chief motivation to vertically integrate with suppliers. This paper expands on that view in building a new theory of vertical integration. In my model firms integrate to gain bargaining power against other suppliers in the production process. The cost of integration is a loss of exibility in choosing the most suitable suppliers for a particular final product. I show that the firms who make the most specific investments in the production process have the greatest incentive to integrate. The theory provides novel insights to the understanding of numerous stylized facts such as the effect of financial development on the vertical structure of firms, the observed pattern from FDI to outsourcing in international trade, the effect of technological obsolescence on organizations, etc.
Keywords: L1; L2; 330; vertical integration; supply chain; bargaining; outside options